I start counting! - Lindop, Audrey Erskine 1920-1986; Kirchin, Basil 1927-2005 (Metro-Goldwyn-Mayer Studios, 2021)
"A 15-year-old girl, coming to terms with her sexuality, suspects that her foster brother may be guilty of the recent murders of young women." [imdb.com]
Original: Großbritannien 1969
Bildformat 1.85:1
licensed from Metro Goldwyn Mayer Studios Inc. and made available in the UK through the British Film Institute
special features: feature newly scanned & restored in 2k from the 35mm interpositive ; "A kickstart: Jenny Agutter remembers 'I start counting!" (2020, 20 mins): a new interview with the actress ; "An apprentice with a master’s ticket" (2021, 40 mins): acclaimed screenwriter Richard Harris looks back over an eclectic career in television and film, ranging from "The avengers" to "A touch of frost" ; "Worlds within worlds" (2021, 33 mins): Jonny Trunk, founder of cult label Trunk Records, revisits the life and art of ambient music pioneer Basil Kirchin ; "I start building" (1942-59, 26 mins): a selection of rare archive films recalling the ‘New Town’ dream ; "Danger on Dartmoor" (1980, 57 mins): plucky kids face peril in this full-length Children’s Film Foundation bonus feature, written by Audrey Erskine Lindop ; "Don’t be like Brenda" (1973, 8 mins): the perennial problem of teenage promiscuity is explored in this cautionary film designed for adolescent viewers ; "Loss of innocence": a video essay on "I start counting" by Chris O'Neill (2020, 8 mins) ; audio commentary by film historian Samm Deighan ; theatrical trailer ; image gallery ; Newly commissioned sleeve artwork by Matt Needle
Keywords: Film; Blu-Ray-Disc